A comparison of benzene-core PCF optical characteristics with hexagonal and circular lattices - Le Tran, Bao Tran; Chu Van, Lanh (Vietnam Journal of Science and Technology, 2025)
This work compares the optical characteristics of benzene photonic crystal fiber with hexagonal lattice (H-PCF) and circular lattice (C-PCF). The difference in the radius between the rings is used to optimize effective area, nonlinearity, attenuation, and chromatic dispersion simultaneously. A series of numerical studies show that the effective mode area and attenuation are small for C-PCF and large for H-PCF geometries. That is the reason why the nonlinear coefficient of H-PCF is larger. Meanwhile, flat dispersion over a wide wavelength range is achieved mostly with H-PCFs in both dispersion modes. Our optimized fibers with near-zero flat dispersion, small loss, and large nonlinearity can enhance supercontinuum generation efficiency to generate a broad spectrum with high coherence.